2008
DOI: 10.1021/ma7022364
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Particle Size and Polymer−Filler Coupling on Viscoelastic Glass Transition of Particle-Reinforced Polymers

Abstract: The viscoelastic glass-to-rubber softening transition is analyzed for various cross-linked polymers reinforced with filler particles. We find that the loss modulus peak corresponding to the segmental relaxation process (glass transition) is not significantly affected by the particle surface area in carbon black-filled polybutadiene or by silane chemical coupling of poly(styrene-co-butadiene) to silica. Large differences in shape and magnitude of the peak in the loss tangent (tan δ) vs temperature are noted for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
199
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 280 publications
(219 citation statements)
references
References 54 publications
20
199
0
Order By: Relevance
“…To characterize the segmental relaxation process, the loss modulus (G ) versus the temperature peak is used rather than the tanδ peak because the latter occurs at higher temperatures and has shape and magnitude which are unduly affected by the rubbery modulus. 21 The dynamic mechanical results presented in Figure 11 corroborate the lack of filler-induced T g change noted by DSC. A review article in this area concludes that there are many such examples for the materials described in Table III.…”
Section: Flocculation Reinforcement and Glass Transition Effects 511supporting
confidence: 67%
See 2 more Smart Citations
“…To characterize the segmental relaxation process, the loss modulus (G ) versus the temperature peak is used rather than the tanδ peak because the latter occurs at higher temperatures and has shape and magnitude which are unduly affected by the rubbery modulus. 21 The dynamic mechanical results presented in Figure 11 corroborate the lack of filler-induced T g change noted by DSC. A review article in this area concludes that there are many such examples for the materials described in Table III.…”
Section: Flocculation Reinforcement and Glass Transition Effects 511supporting
confidence: 67%
“…[16][17][18] There are observations that the segmental relaxation (α-relaxation) and glass transition temperature (T g ) are not significantly affected by the presence of filler, despite significant levels of "bound" polymer from chemically modified polymer-filler interfaces and from well dispersed particles with high surface area. [19][20][21][22][23][24] On the other hand, there are other reports which show that the filler can have a significant influence on the glass transition dynamics. [25][26][27][28][29][30][31] In particular, the research of Tsagaropoulos and Eisenberg 25,26 is often cited as support for the existence of severely retarded segmental motion of the polymer near the surfaces of small particles (glassy polymer shell).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic mechanical testing is a common technique to study the effect of particles on the T g of polymers, [11][12][13][14][15][16][17][18][19][20][21][22][23] and a summary of these studies is given in Table I. Many investigators draw conclusions based on the temperature of the maximum in the isochronal loss tangent, tanδ = G"/G' (abbreviations are defined in the appendix).…”
Section: Dynamic Mechanical Spectroscopymentioning
confidence: 99%
“…Many investigators draw conclusions based on the temperature of the maximum in the isochronal loss tangent, tanδ = G"/G' (abbreviations are defined in the appendix). This can be problematic because tanδ in the glass-to-rubber softening region is influenced not only by the local segmental dynamics, as reflected in the magnitude of the loss modulus toward lower T, but also by filler-induced changes in both G' and G" at higher T. As shown recently by Robertson et al for BR reinforced with carbon black or SBR reinforced with silica, 23 the shape and position of the loss modulus peak are unaffected by particle surface area and the intensity of the polymer-filler interaction, despite substantial changes in the loss tangent peaks (see Figure 1). Vieweg et al 21 also reported negligible modification of the segmental relaxation behavior in filled SBR, as illustrated in Figure 2.…”
Section: Dynamic Mechanical Spectroscopymentioning
confidence: 99%